Implementation of Article 17 Paragraph (1) of Lampung Governor's Regulation Number 36 of 2025 concerning cassava governance and downstream from the perspective of Siyasah Tanfidziyah - Agung Romadon; Relit Nur Edi; Iip Nuruul Topani (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
This study aims to analyze the implementation of Article 17 Paragraph (1) of the Lampung Governor's Regulation Number 36 of 2025 concerning Cassava Governance and Downstream and review it from the perspective of Siyasah Tanfidziyah. The article regulates the obligation of local governments to supervise the purchase or receipt of cassava stalls in order to create an orderly, fair, and protective trading system for farmers. This research uses a qualitative method. Data was obtained through interviews, observations, and documentation involving village heads, cassava stalls, and farmers in Sinar Rejeki Village, Jati Agung District, South Lampung Regency. The data was analyzed descriptively by linking the field findings with the provisions of laws and regulations and the theory of Siyasah Tanfidziyah.The results of the study showed that the implementation of Article 17 Paragraph (1) had not been running optimally. Supervision of business licensing, weighing marks, cassava quality, and trade systems still faces various obstacles, such as lack of coordination between agencies, limited field supervision, low awareness of business actors on business legality, and weak enforcement of sanctions for violations. This condition has led to the discovery of stalls operating without permits, a lack of transparency in transactions, and potential losses for farmers. Viewed from the perspective of Siyasah Tanfidziyah, the implementation of this policy has not fully reflected the principles of trust, justice, maslahah, hisbah, and tanfidz al-ahkam because supervision and enforcement of rules have not been carried out optimally. Therefore, it is necessary to strengthen supervision, improve coordination between agencies, continuous socialization, and stricter law enforcement so that the goals of cassava governance and downstream can be realized effectively and provide benefits to the community.